Integrating Ionic Electroactive Polymer Actuators and Sensors Into Adaptive Building Skins – Potentials and Limitations - Neuhaus, Raphael; Zahiri, Nima; Petrs, Jan; Tahouni, Yasaman; Siegert, Jörg; Kolaric, Ivica; Dahy, Hanaa; Bauernhansl, Thomas (Frontiers in Built Environment, 2020)
Building envelopes separate the confined interior world engineered for human comfort and indoor activity from the exterior world with its uncontainable climatic forces and man-made immission. In the future, active, sustainable and lightweight building skins are needed to serve as an adaptive interface to govern the building-physical interactions between these two worlds. This article provides conceptual and experimental results regarding the integration of ionic electroactive polymer sensors and actuators into fabric membranes. The ultimate goal is to use this technology for adaptive membrane building skins. These devices have attracted high interest from industry and academia due to their small actuation voltages, relatively large actuation and sensing responses and their flexible and soft mechanical characteristics. However, their complex manufacturing process, sophisticated material compositions and their environmental sensitivity have limited the application range until now. The article describes the potentials and limitations of employing such devices for two different adaptive building functionalities: first, as a means of ventilation control and humidity regulation by embedding small actuated apertures into a fabric membrane, and second, as flexible, energy- and cost-efficient distributed sensors for external load monitoring of such structures. The article focusses on designing, building and testing of two experimental membrane demonstrators with integrated polymer actuators and sensors. It addresses the challenges encountered and draws conclusions for potential future optimization at the device and system level.